Efek Deferiprone dan Ekstrak Buah Phaleria macrocarpa terhadap Akumulasi Zat Besi pada Ginjal Tikus - Wahyudy, Silvy; Haniifa, Saalima Nur; Estuningtyas, Ari (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Iron overload can cause oxidative stress and kidney damage by increasing reactive oxygen species (ROS) and decreasing antioxidant defenses, including total glutathione (T-GSH). Chelation therapy with deferiprone (DFP) as a standard treatment and ethanolic Phaleria macrocarpa (PM) fruit extract as a natural alternative is expected to lower renal iron buildup and restore redox balance. This study aimed to assess the effects of DFP, PM, and their combination on renal iron and T-GSH levels in a rat model of iron overload. Methods A total of 30 male Sprague-Dawley rats were randomly assigned to six groups (N, IO, D, PM, DPM-1, DPM-2). Iron overload was induced by intraperitoneal injections of iron-dextran (0.3 mL, approximately 15 mg Fe) twice weekly for three weeks, followed by five weeks of daily oral treatments. Renal iron levels were measured using atomic absorption spectrophotometry (λ 248.3 nm), and T-GSH was quantified colorimetrically (λ 412 nm). Iron data were analyzed with one-way ANOVA and LSD post-hoc test, while T-GSH levels were evaluated using the Mann-Whitney U test (p < 0.05). Results Renal iron levels were highest in the DPM-1 group at 50.46 ± 22.31 mg/kg, which is 1.95 times above normal; however, one-way ANOVA showed no statistically significant differences among groups (p = 0.490). T-GSH levels did not vary significantly across most treatments, except for a notable increase in the DPM-1 group compared to PM (Mann-Whitney, p = 0.034). Conclusions The DPM-1 combination shows a potential synergistic effect in increasing renal T-GSH levels, although it has not significantly lowered iron levels in the lower-dose DFP and PM combination (DPM-2). Additional studies with longer treatment periods and more antioxidant parameters are necessary to assess the protective potential of DFP-PM combinations against oxidative stress and renal ferroptosis caused by iron overload.